Trend of Islamic housing financing in Bank Simpanan Nasional (BSN), Jalan Munshi Abdullah, Melaka / Nur Amerul Alias - Alias, Nur Amerul (2011)
Islamic house financing has been introduced and implemented in Bank Simpanan Nasional, Melaka since 2003. However, we do not know how far justifications level of consumer acceptance and perception of this Islamic product. This study deals with several factors namely, interest rate, bank services and lack of customer awareness towards purchase decision on Islamic house financing product in Bank Simpanan Nasional, Melaka. In this study, the researcher collects the information about customer acceptance from interview, questionnaire, observation, website and secondary data such as journal, article, annual report and also newspaper. This study will help Bank Simpanan Nasional Melaka to identify their weakness in order to examine the factors that influence consumers in adopting Islamic home financing products in Bank Simpanan Nasional Melaka. Quantitative method has been used in this research in order to see how far that Islamic house financing product can be fully accepted by consumer in Bank Simpanan Nasional Melaka. 40 questionnaires have been distributed to the respondent in Bank Simpanan Nasional Melaka. Researcher found that these three factors namely interest rate, bank services and lack of customer awareness has strong relationship that influenced customer purchase decision on Islamic house financing products in Bank Simpanan Nasional Melaka. Based on data analysis received from the respondents who intends to apply Islamic house financing, it can be identified that overall factors of interest rate, bank services and lack of customer awareness gives positive significant influence to consumer’s decision to choose Islamic house financing in Bank Simpanan Nasional, Melaka. In conclusion, some suggestion and strategies have been made to minimize the issue arises in Bank Simpanan Nasional Melaka relating to Islamic housing financing. This is important because it will help Bank Simpanan Nasional Melaka to improve their Islamic product service and it will affect the level of customer satisfaction towards Islamic housing financing in Bank Simpanan Nasional Melaka.